2003
DOI: 10.1046/j.1099-1123.2003.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Audit Committee and the Internal Audit Function: Evidence from Australia and New Zealand

Abstract: This study examines the separate influence of independence and financial experience on audit committee relations with the internal audit function. Using data from Australia and New Zealand, the study focuses on audit committees and internal audit in both private and public sector entities. Data were collected by means of a questionnaire sent to chief internal auditors. The results suggest that independence and accounting experience have a complementary impact on audit committee relations with internal audit. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 8 publications
14
150
1
4
Order By: Relevance
“…264. ), Australia and New Zealand (Goodwin, 2003). The above-mentioned studies were mainly focused on determining the influence of independence of the audit committee members on the relationship between the audit committee and the internal audit function (Goodwin & Yeo, 2001;Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264), then determining, separately, the influence of the independence of the members and their competence in the area of accounting and/or finance on the relationship between the audit committee and the internal audit function (Goodwin, 2003); that is, determining, altogether, the influence of independence and competence of the audit committee members (Raghunandan et al, 2001;quoted in Goodwin, 2003, p. 264) on the relationship of the audit committee and the internal audit function (Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264).…”
Section: The Relation Between Internal Auditing and The Audit Committeementioning
confidence: 99%
See 1 more Smart Citation
“…264. ), Australia and New Zealand (Goodwin, 2003). The above-mentioned studies were mainly focused on determining the influence of independence of the audit committee members on the relationship between the audit committee and the internal audit function (Goodwin & Yeo, 2001;Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264), then determining, separately, the influence of the independence of the members and their competence in the area of accounting and/or finance on the relationship between the audit committee and the internal audit function (Goodwin, 2003); that is, determining, altogether, the influence of independence and competence of the audit committee members (Raghunandan et al, 2001;quoted in Goodwin, 2003, p. 264) on the relationship of the audit committee and the internal audit function (Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264).…”
Section: The Relation Between Internal Auditing and The Audit Committeementioning
confidence: 99%
“…), Australia and New Zealand (Goodwin, 2003). The above-mentioned studies were mainly focused on determining the influence of independence of the audit committee members on the relationship between the audit committee and the internal audit function (Goodwin & Yeo, 2001;Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264), then determining, separately, the influence of the independence of the members and their competence in the area of accounting and/or finance on the relationship between the audit committee and the internal audit function (Goodwin, 2003); that is, determining, altogether, the influence of independence and competence of the audit committee members (Raghunandan et al, 2001;quoted in Goodwin, 2003, p. 264) on the relationship of the audit committee and the internal audit function (Scarbrough et al, 1998;quoted in Goodwin, 2003, p. 264). Goodwin and Yeo (2001) have been researching the relationship of the audit committee and the internal audit operations in Singapore and they concluded that there is a higher probability that an audit committee consisting exclusively of non-executive members has a higher interaction with the internal audit function then those audit committees that consist of executive members, i.e., the frequency of meetings between audit committees and internal audit functions and probability of private meetings between them, without the presence of management, is higher in the situation when all members of the audit committee are non-executive members.…”
Section: The Relation Between Internal Auditing and The Audit Committeementioning
confidence: 99%
“…Some recent studies have also explored the relationship between internal audit and the audit committee (Goodwin, 2003;Raghunandan et al, 2001;Goodwin and Yeo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with Canadian study of [23] reported that 48 percent of the respondents indicated that AC are involved in the dismissal of the IAF. [12] reported 72 percent in Singapore, [20] reported 50 percent of AC are involved in the appointment evaluation and dismissal of internal audit head in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…There were 41 responses from the private sector organizations representing 60.29 percent and 27 responses from public sector representing 39.17 percent. The questionnaire was structure following previous studies with little modification [13], [20]- [22] each question was designed to incorporate responses expressed in multiple choices that enabled the respondents to express their opinion.…”
Section: Methodsmentioning
confidence: 99%